Cognitive alterations secondary to traumatic brain injury in the pediatric population - Santrich-Sotomayor, Madeleine (2023)
Traumatic brain injury is a prevalent condition in our environment, causing disabling impairments in affected individuals. While there are numerous reports on sensorimotor alterations in the adult population, there is a significant dearth of literature concerning pediatric populations who experience head trauma and the resulting cognitive sequelae, which can profoundly affect their development. This review aims to consolidate information from the past two decades regarding cognitive impairments following traumatic brain injury in children. The emphasis is placed on cognitive functions that undergo critical periods or vulnerable windows during childhood, such as language, memory, attention, and inhibitory control. The impairments identified in these functions may account for the negative impact of traumatic brain injury on processes like learning, the establishment of social cognition, and the development of school-related skills. These long-term consequences can significantly influence an individual's future prospects, including their ability to secure employment and achieve social inclusion.